INTERAÇÃO ENTRE O GRUPO HEME E A ARTEMISININA - Araújo, Jockley Queiroz (2007)
Malaria is an infectious disease caused by the unicellular parasite Plasmodium sp. Currently, the malaria parasite acquired resistance to the traditional pharmacological alternatives, which became ineffective. So, beginning with a screening in traditional chinese drugs, researchers isolated artemisinin from an herb belonging to the Asteraceae family named Artemisia Annua L. whose antimalarial activity was described in 1596. Studies showed that administration of artemisinin to patients with malaria caused a clinical improvement and elimination of parasita in the blood in two days. It has been suggested that the antimalarial activity of artemisinin is due to the interaction of its peroxide group with the prostetic heme group of human hemoglobin, leading to citotoxic species which may be responsible the parasite s death. Thus, with the objective of improving the understand of the mechanism of action of artemisinin, we simulated the interaction processes between heme group and the artemisinin molecule by means of Density Functional Theory calculations. We determined the interaction energies, the most stable electronic states and the geometrical arrangement for the thermodynamically most stable complex between the heme group and artemisinin. The results show that for in interaction between the heme group and artemisinin at long distance, the complex in the quintuplet state is more stable than those in the septuplet and in the triplet states by 17.4 kcal/mol e 37.99 kcal/mol, respectively. However, for interaction at short distance, the calculations showed that the most stable complex has a septuplet spin state. These results obtained in the present work agree with the mechanism of action as proposed in the literature, which suggests a favorable interaction between artemisinin and heme.